Characterization of the Catalytic Domain of Clostridium novyi Alpha-Toxin - Busch, Christian (American Society for Microbiology, 2000)
Clostridium novyi alpha-toxin belongs to the family of large clostridial cytotoxins which act on cells through the modification of small GTP-binding proteins. We present here an analysis of the catalytic domain of alpha-toxin. A NH(2)-terminal 551-amino-acid fragment, α551, was found to contain the full enzyme activity of the holotoxin, whereas a slightly shortened fragment encompassing 509 amino acids showed no detectable enzyme activity. Further characterization of the enzymatically active fragment α551 revealed a substrate specificity for both UDP–N-acetylglucosamine and UDP-glucose. A Michaelis-Menten constant of 17 μM was determined for the substrate UDP–N-acetylglucosamine, while that for UDP-glucose was about 20 times higher, indicating a weaker affinity of the toxin for the latter substrate. Mutation of the aspartic acids of a conserved motif DXD within α551 reduced enzyme activity >700-fold and inhibited cytotoxicity after microinjection in cells. Inhibition of enzyme activity of the DXD mutant could be partially overcome by increased concentrations of manganese ions, suggesting the involvement of these aspartic acids in Mn(2+) binding. By construction of chimeras of enzymatically active fragments of C. sordellii lethal toxin and C. novyi alpha-toxin, we located the region involved in nucleotide-sugar specificity to amino acids 133 through 517.